Realistic elbow flesh deformation based on anthropometrical data for ergonomics modeling - Setia Hermawati; Russell Marshall (2009)
The human model for ergonomic simulation has improved in terms of its reliability and appearance and yet there seems to be less attention paid to create a realistic and accurate flesh deformation around the joint. This study, a part of ongoing research, proposes a combination of manual and automatic (3D body scanner) measurements to create a database for flesh deformation prediction i.e. flesh deformation area and cross section changes, around the elbow joint. The database consists of two race groups i.e., Caucasian and Asian (23 subjects, 11 males and 12 females), which were carefully chosen to represent a variety of height and body type. The prediction results for both flesh deformation area and cross section changes are discussed as well as their relevance for the next stage of the study.